Demographic Differences Among Patients Undergoing Blepharoplasty Based on Surgeon Training in New York State. Issue 1 (January 2020) - Gorbea, Enrique; Legocki, Alex T.; Gray, Mingyang; Yang, Anthony; Schwarcz, Robert; Iloreta, Alfred; Rosenberg, Joshua D.
Abstract : Purpose: To evaluate whether patient demographics and surgical metrics varied among differently trained surgeons performing blepharoplasty. Methods: The Statewide Planning and Research Cooperative System database was used to identify patients who underwent blepharoplasty in New York State. Surgeons were grouped based on residency training as listed in the New York State Physician Profile. Multivariate regression analysis was used to determine predictors of patient characteristics based on surgeon training. Results: There were 361 surgeons who performed 39, 932 cases of blepharoplasty in New York State from 2008 to 2016. When aggregated by surgeon training, there were significant differences among procedure times and total charges for blepharoplasty. On average, cases performed by ophthalmologists took 66.7 minutes and patients were charged $6, 860; cases performed by otolaryngologists took 158.2 minutes and patients were charged $9, 084; and cases performed by plastic surgeons took 131.8 minutes and patients were charged $11, 028. Unlike plastic surgeons or otolaryngologists, ophthalmologists tended to have older patients and more male patients. Ophthalmologists were more likely to operate on patients with comorbidities as well as non-white patients ( p < 0.0001). They were also significantly more likely to have patients with insurance coverage than self-pay ( p < 0.0001). Conclusions: Demographic and surgical metrics of blepharoplasty cases performed by surgeons trained in otolaryngology and plastic surgery are similar. Ophthalmology-trained surgeons performed blepharoplasty on patients that were more likely to be older, male, non-white, and had insurance coverage. Ophthalmologist procedure time for blepharoplasty was also less than half of the procedure time of otolaryngologists and plastic surgeons. Blepharoplasty is a surgical procedure commonly performed by ophthalmologists, otolaryngologists, and plastic surgeons to address cosmetic concerns or visual impairment related to the eyelids.